Influence of Silver Nanoparticles on Selected Properties of Dental Porcelain: An in vitro study - Hamdy, Noha; Hussen, Yasser F. (Open Access Macedonian Journal of Medical Sciences, 2022)
This study was conducted to reveal antibacterial effect of silver nanoparticles incorporation on dental porcelain and its effect on flexural strength and surface hardness of porcelain.